3‐photon microscopy of myelin in mouse digital skin excited at the 1700‐nm window. Issue 12 (1st October 2020) - He, Chen; Deng, Xiangquan; Pan, Yi; Tong, Shen; Kang, Jiayu; Li, Jia; Qiu, Ping; Wang, Ke
Abstract: Myelin is a key component of the peripheral nervous system, whose structure anomaly in the digital skin is implicated in neuropathy. Here we demonstrate an in vivo labeling and imaging technique, capable of visualizing myelin sheaths deep in the mouse digital skin. Through material characterization, we verify that 3‐photon fluorescence (3PF) can be generated from a commonly used dye‐ FluoroMyelin Red for labeling myelin, excited at the 1700‐nm window. Topical injection of FluoroMyelin Red in the mouse digit leads to bright labeling of myelin sheaths. Harnessing the deep‐penetration capability of 3‐photon microscopy excited at the 1700‐nm window, we demonstrate that 3PF imaging of FluoroMyelin Red‐labeled myelin sheaths in the mouse digit in vivo can be achieved to a depth 340 μm below the skin surface, revealing both branching bundle of and individual myelin sheaths. Abstract : 3‐photon microscopy excited at the 1700‐nm window and Fluoromyelin Red labeling enable deep imaging of myelin sheaths in the mouse digital skin in vivo.